2017
DOI: 10.1371/journal.pcbi.1005408
|View full text |Cite
|
Sign up to set email alerts
|

Human behavioral complexity peaks at age 25

Abstract: Random Item Generation tasks (RIG) are commonly used to assess high cognitive abilities such as inhibition or sustained attention. They also draw upon our approximate sense of complexity. A detrimental effect of aging on pseudo-random productions has been demonstrated for some tasks, but little is as yet known about the developmental curve of cognitive complexity over the lifespan. We investigate the complexity trajectory across the lifespan of human responses to five common RIG tasks, using a large sample (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 54 publications
1
50
0
3
Order By: Relevance
“…We have introduced a new approach to the study of the behaviour of animals and humans based on algorithmic information theory. We have shown that humans best outsmart computers when they are tested on randomness generation at the age of 25 [4]. When competing against all possible algorithms, we have found that human behaviour is at its most algorithmically random at 25 years of age, thereby introducing a new measure of cognitive complexity possibly related to other biological and cultural phenomena, such as creativity.…”
Section: Algorithmic Intelligencementioning
confidence: 99%
“…We have introduced a new approach to the study of the behaviour of animals and humans based on algorithmic information theory. We have shown that humans best outsmart computers when they are tested on randomness generation at the age of 25 [4]. When competing against all possible algorithms, we have found that human behaviour is at its most algorithmically random at 25 years of age, thereby introducing a new measure of cognitive complexity possibly related to other biological and cultural phenomena, such as creativity.…”
Section: Algorithmic Intelligencementioning
confidence: 99%
“…So we can reasonably hope that similar tools will approximate logical depth (see e.g. Zenil, Delahaye, and Gaucherel 2012;Gauvrit et al 2017).…”
Section: Organized Complexity and Traditional Ethical Issuesmentioning
confidence: 99%
“…An example illustrating how to achieve this in the context of, e.g., a Bayesian approach, has been provided in [45] and consists in replacing the uninformative prior by the uninformative algorithmic probability distribution, the so-called Universal Distribution, as introduced by Levin [20]. The general approach has already delivered some important results [46] by, e.g., quantifying the degree of human cognitive randomness that previous statistical approaches and measures such as Entropy made it impossible to quantify. Animated videos have been made available explaining applications to graph complexity (https://youtu.be/E238zKsPCgk) and to cognition in the context of random generation tasks (https://youtu.be/E-YjBE5qm7c).…”
Section: An Algorithmic Maximum Entropy Modelmentioning
confidence: 99%